(untitled) (Biological Sciences - PJSIR, 2005)
Concentrations and distribution of seven heavy metals, namely, Pb, Cd, Zn, Cr, Co, Ni and Cu in the soil samples collected from 38 different sites from Ibadan Metropolis and its suburbs were investigated. The metals were extracted from the soil with HNO -HClO -HF combination for the elemental analysis using flame atomic absorption spectrophotometer. 3 4 The results obtained for all locations indicated (mg g-1 dry weight): Pb (150±143); Cd (4.2±4.4); Zn (213±213); Cr (131±96); Co (38±19); Ni (79±56); and Cu (40±36). Zonal average of metal concentrations indicated the highest metal load in the environment of the urban high traffic (UHT) zone followed by the refuse dump sites. Interelemental association in the UHT-zone showed significant correlation between the pairs Pb-Cd (r = 0.521), Pb-Cu (r=0.412), Zn-Cr (r = 0.603), Zn-Cu (r = 0.334), Ni-Cr (r = 0.749), Ni-Co (r =0.324), and Cd-Cu (r = 0.408).